Characterization of Two Extracellular Polysaccharides from Marine Bacteria - Boyle, C. David (1983)
Two bacterial isolates from the intertidal zone produced significant quantities of extracellular polysaccharide with interesting properties. One polysaccharide was named PS 3a24; the other was named PS 3a35. The relative proportion of sugars in PS 3a35 was 51.6% glucose, 39.0% galactose, 3.1% mannose, and 6.3% rhamnose, with a trace of an unidentified sugar. PS 3a24 was composed of 40.2% glucose, 57.2% galactose, and 2.6% mannose. PS 3a35 contained 6% pyruvate, whereas PS 3a24 contained no pyruvate. Both exhibited high specific viscosity, pseudoplasticity, and stability over a wide range of pH in the presence of a variety of salts. The viscosity of PS 3a35 was relatively insensitive to increasing temperature, whereas that of PS 3a24 showed an irreversible drop on heating.